2013
DOI: 10.1016/j.ijgo.2013.07.009
|View full text |Cite
|
Sign up to set email alerts
|

There are some questions you may not ask in a clinic: Providing contraception information to young people in Kenya using SMS

Abstract: a b s t r a c t a r t i c l e i n f oObjective: To evaluate the acceptability, information access, and potential behavioral impact of providing contraception information via text message on mobile phones to young people in Kenya. Methods: Three methods of data collection were implemented during the 17-month pilot period for the Mobile for Reproductive Health (m4RH) program in Kenya: automatic logging of all queries to the m4RH system; demographic and behavior change questions sent via short message service pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
108
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(111 citation statements)
references
References 9 publications
2
108
0
1
Order By: Relevance
“…These results seem to be consistent with previous studies [13, 2830] which found privacy and confidentiality of young people during family planning and counselling as important determinants of use of services. The lack of youth engagement strategies and low cost/discounted RHC services to adolescents was apparent in both public and private RHC facilities.…”
Section: Discussionsupporting
confidence: 93%
“…These results seem to be consistent with previous studies [13, 2830] which found privacy and confidentiality of young people during family planning and counselling as important determinants of use of services. The lack of youth engagement strategies and low cost/discounted RHC services to adolescents was apparent in both public and private RHC facilities.…”
Section: Discussionsupporting
confidence: 93%
“…An SMS contraceptive education scheme in Kenya suggested improved contraceptive knowledge and use, but suffered from a sample size that was too small, with no control group, thus reducing the ability to draw firm conclusions (22). A Peruvian RCT, using educational SMS to reduce risks of contracting dengue fever, hinted at improved educational equity via SMS but showed no statistically significant improvement over alternative educational schemes (54).…”
Section: Resultsmentioning
confidence: 99%
“…Reaching young people with information on contraceptives through mobiles phones in Kenya and promoting condom sales and use through a mixture of digital platforms – including Facebook – in Turkey have proven to be effective [23,24]. …”
Section: Discussionmentioning
confidence: 99%